Adducin polymorphisms and the treatment of hypertension. (May 2007) - Manunta, Paolo; Citterio, Lorena; Lanzani, Chiara; Ferrandi, Mara
Hypertension is an important public health problem affecting more than 50  million individuals in the USA alone. The most common form, essential hypertension, results from the complex interplay between genetic predisposition and environmental influences. Epidemiological, migration, intervention and genetic studies in humans and animals provide very strong evidence of a causal link between high salt intake and high blood pressure. One of the candidate genes for salt-sensitive hypertension is adducin. Adducin is a heterodimeric cytoskeleton protein, the three subunits of which are encoded by genes ( ADD1, ADD2 and ADD3 ) that map to three different chromosomes. A long series of parallel studies in the Milan hypertensive rat strain model of hypertension and humans indicated that an altered adducin function might cause hypertension through enhanced constitutive tubular sodium reabsorption. An example of a prospective efficacy of pharmacogenetics and pharmacogenomics is the detection and impact of adducin polymorphisms on hypertension. In particular, the selective advantages of diuretics in preventing myocardial infarction and stroke over other antihypertensive therapies that produce a similar blood pressure reduction in carriers of the mutated adducin may support new strategies aimed at optimizing the use of new antihypertensive agents for the prevention of hypertension-associated organ damage.